Calidad de vida y discapacidad en pacientes de 18 a 65 años con Lumbalgia - Enma Molina Amaya; Anayansy Madelem Rivera Díaz; Ismael Alberto García Morales; Paola Ochoa; Edna J. Maradiaga (Revista Médica Hondureña)
Introduction: Low back pain is a public health problem that affects Quality of Life (QoL) and generates disability. Objective: To determine QoL and disability in patients with low back pain at the Honduran Institute of Social Security (IHSS) in Tegucigalpa, from May to July 2021. Methods: Cross-sectional descriptive study, 165 patients from the Specialised Centre of Physical Medicine and Rehabilitation with a diagnosis of low back pain were evaluated. The clinical characteristics of low back pain, CV with Short Form Health Survey (SF-12) 1.0 scale and disabil-ity with Oswestry index (ODI) 1.0 were measured. Analysis was performed by calculating frequencies and percentages for qualita-tive variables and measures of central tendency for quantitative variables. Statistical tests were used: Spearman, Student’s t-test and Mann-Whitney, p-value <0.05 was significant. The protocol was approved by the Ethics Committee. Results: Median age: 42 years, interquartile range (IQR 34-53); female sex predominated with 62.4%; median CV score 44.9 (IQR 35.9-52.9). A moderate correlation was found between ODI and physical QoL (r=-0.52) and mental QoL (r=-0.44). Less physical activity, constant, radiating and severe pain were more disabling than other conditions (10.3, 11.4, 14.2 and 19.2 ODI points respectively). Physical QoL was heterogeneously affected and mental QoL was affected by radi-ating pain (7 points less in SF-12). Discussion: Low back pain affects QoL, leading to disability in economically active people. It is important to reinforce interdisciplinary management and identify risk factors in order to apply preventive actions.